A slurry viscosity regulation method, a regulation system and an electrode tab preparation process
Patent Information
- Application Number
- CN202611096545.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-27
AI Technical Summary
在此过程中,液相法工艺波动会导致各个批次的磷酸铁锂原料在碳包覆层厚度与微观结构存在本征差异,进而导致制备得到的正极浆料粘度产生差异,而正极浆料的粘度差异将会直接影响正极极片的涂布质量以及后续制得的电池的一致性
[0033]浆料涂布,将正极浆料涂布在正极集流体上以形成正极极片粗料。
Smart Images

Figure CN122984807A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery manufacturing technology, specifically to a slurry viscosity control method, control system, and electrode preparation process. Background Technology
[0002] With the rapid development of new energy-related technologies, the application of new energy batteries, represented by lithium-ion batteries, is becoming more and more widespread. At the same time, the wider range of application scenarios has also put forward higher requirements for the performance of new energy batteries.
[0003] In the industrial production of lithium batteries, lithium iron phosphate is typically synthesized first using a liquid-phase method, followed by the preparation of the cathode slurry. During this process, fluctuations in the liquid-phase method can lead to intrinsic differences in the carbon coating thickness and microstructure of different batches of lithium iron phosphate raw materials. This, in turn, results in differences in the viscosity of the prepared cathode slurry. The viscosity difference of the cathode slurry directly affects the coating quality of the cathode sheet and the consistency of the subsequently manufactured batteries.
[0004] In existing technologies, the viscosity of the prepared cathode slurry is adjusted by fixing the formula and then manually adjusting it afterward. However, this method is not only inefficient and may require repeated adjustments, but it also easily leads to waste of raw materials and increased costs.
[0005] Therefore, there is an urgent need to provide a process for preparing or controlling the positive electrode slurry, which can precisely adjust the viscosity of the prepared positive electrode slurry in advance, and achieve efficient and accurate slurry viscosity adjustment to improve the coating quality of the positive electrode sheet and the consistency of the manufactured battery. Summary of the Invention
[0006] The purpose of this application is to provide a slurry viscosity control method, control system, and electrode preparation process, which can accurately adjust the viscosity of the prepared positive electrode slurry in advance, and achieve slurry viscosity adjustment efficiently and accurately, so as to improve the coating quality of the positive electrode and the consistency of the manufactured battery.
[0007] To achieve the above objectives, in a first aspect, this application provides a method for controlling the viscosity of a slurry, the method comprising: Raw material testing involves determining the actual graphitization order of lithium iron phosphate raw materials.
[0008] Raw material classification involves comparing the actual graphitization order of lithium iron phosphate raw materials with a preset range to classify them into different viscosity tendency categories.
[0009] Solvent compensation is determined based on the viscosity tendency of the lithium iron phosphate raw material and its difference from a preset range.
[0010] The compensation process involves controlling the feeding of materials in the batching unit to prepare the slurry based on the determined solvent compensation amount.
[0011] Based on the above embodiments of this application, the graphitization order of lithium iron phosphate raw materials is measured before slurry preparation. The lithium iron phosphate raw materials are classified into different viscosity tendency categories according to the graphitization order. During slurry preparation, the graphitization order of lithium iron phosphate raw materials will directly affect the viscosity of the prepared slurry.
[0012] Specifically, on the one hand, when the graphitization order of lithium iron phosphate raw materials is higher, the particles in the lithium iron phosphate raw materials are more likely to agglomerate to form larger secondary particle agglomerates. At this time, the large-sized secondary particle agglomerates will increase the resistance to particle movement in the slurry, thereby increasing the slurry viscosity. Conversely, the slurry viscosity will decrease.
[0013] On the other hand, the higher the graphitization order of lithium iron phosphate raw materials, the higher the carbon content on the surface of lithium iron phosphate raw materials, and the more ordered and dense the carbon layer structure formed, which makes the interaction force between lithium iron phosphate particles and solvent stronger, thus making the viscosity of the prepared slurry higher, and vice versa.
[0014] As shown above, by detecting the graphitization degree of lithium iron phosphate raw materials, the viscosity of the prepared slurry can be effectively determined, allowing for solvent compensation in advance. For lithium iron phosphate raw materials with high graphitization degree, positive solvent compensation is performed by increasing the solvent content to reduce the viscosity of the prepared slurry. For lithium iron phosphate raw materials with low graphitization degree, negative solvent compensation is performed by reducing the solvent content to increase the viscosity of the prepared slurry. For lithium iron phosphate raw materials with graphitization degree within a preset range, the standard amount of solvent can be added. Ultimately, this ensures that the viscosity of the slurry prepared from different lithium iron phosphate raw materials tends to be consistent, guaranteeing the stability of the slurry viscosity.
[0015] In summary, this application pre-detects the graphitization order of lithium iron phosphate raw materials and pre-determines the viscosity of the prepared slurry based on the graphitization order of the lithium iron phosphate raw materials. Subsequently, when the slurry preparation begins, compensation adjustments can be made by adjusting the amount of solvent added, so that the viscosity of the slurry prepared from different lithium iron phosphate raw materials can tend to be consistent, ensuring the stability of the slurry viscosity, guaranteeing the coating quality of the electrode sheets, and ensuring the consistency of the batteries subsequently prepared.
[0016] In some embodiments, during the raw material classification step, the actual graphitization order of the lithium iron phosphate raw material is divided into three categories according to a preset range: a high viscosity tendency category, a baseline category, and a low viscosity tendency category. Specifically, in the high viscosity tendency category, the graphitization order of the lithium iron phosphate raw material is greater than the preset range; in the baseline category, the graphitization order of the lithium iron phosphate raw material is within the preset range; and in the low viscosity tendency category, the graphitization order of the lithium iron phosphate raw material is less than the preset range.
[0017] Based on the embodiments described above, lithium iron phosphate raw materials are specifically divided into three categories according to their graphitization degree. Specifically, a baseline category is first determined, and the viscosity of the slurry prepared from lithium iron phosphate raw materials within this baseline category corresponds to the baseline viscosity. Then, lithium iron phosphate raw materials with a graphitization degree greater than the baseline category are classified into a high viscosity tendency category. The slurry viscosity prepared from lithium iron phosphate raw materials in this category will be greater than the baseline viscosity; therefore, in subsequent preparation, it is necessary to reduce the viscosity of the prepared slurry by increasing the solvent. Finally, lithium iron phosphate raw materials with a graphitization degree less than the baseline category are classified into a low viscosity tendency category. The slurry viscosity prepared from lithium iron phosphate raw materials in this category will be less than the baseline viscosity; therefore, in subsequent preparation, it is necessary to increase the viscosity of the prepared slurry by reducing the solvent.
[0018] In some embodiments, the Raman spectrum of lithium iron phosphate feedstock in the high viscosity tendency category shows I... D / I G ≤0.85, in the Raman spectrum of lithium iron phosphate raw materials in the benchmark category, 0.85 < I D / I G <0.9, the Raman spectrum of lithium iron phosphate raw materials in the low viscosity tendency category has I D / I G ≥0.9.
[0019] Based on the above embodiments of this application, using the I in the Raman spectrum of lithium iron phosphate raw material... D / I G The value reflects the graphitization order of lithium iron phosphate raw materials. Specifically, Raman spectroscopy can be used for detection, thereby achieving standardized and precise detection of the graphitization order of lithium iron phosphate raw materials, and thus improving the accuracy of subsequent control processes.
[0020] In some embodiments, during the solvent compensation step, the actual amount of solvent added is determined according to the following formula (1): (1) Where m is the actual amount of solvent added, m0 is the theoretical amount of solvent added, and k is the control coefficient, which is set to 1500. For lithium iron phosphate feedstock in the benchmark category I D / IG With the lithium iron phosphate raw material I D / I G The difference.
[0021] Based on the above embodiments of this application, a specific formula for determining the actual amount of solvent added is disclosed. In the specific calculation, the theoretical amount of solvent to be added is first determined, and then based on the I value of lithium iron phosphate raw materials in the benchmark category... D / I G With the lithium iron phosphate raw material I D / I G The solvent compensation amount is calculated based on the difference. For lithium iron phosphate raw materials with high viscosity tendency, the slurry viscosity is reduced by increasing the solvent, while for lithium iron phosphate raw materials with low viscosity tendency, the slurry viscosity is increased by reducing the solvent, ultimately making the viscosity of the prepared slurry tend to be consistent.
[0022] In some embodiments, the theoretical amount of solvent added, m0, is in a mass ratio of 1:10 to the lithium iron phosphate raw material.
[0023] Based on the above embodiments of this application, when calculating the actual amount of solvent added, the theoretical amount of solvent added is first quickly determined according to the above ratio, and then the theoretical amount of solvent added is substituted into the above formula to determine the actual amount of solvent added.
[0024] In some embodiments, calculation At that time, the I value of lithium iron phosphate raw materials in the benchmark category corresponding to the high viscosity tendency category is... D / I G The value is 0.86, which is the I value of lithium iron phosphate raw materials in the benchmark category corresponding to the low viscosity tendency category. D / I G The value is 0.89.
[0025] Based on the above embodiments of this application, when determining the actual amount of solvent added, it is necessary to consider the I value of lithium iron phosphate raw materials in the benchmark category. D / I G Value and actual lithium iron phosphate raw material I D / I G The difference is calculated using the value. Specifically, when the actual lithium iron phosphate raw material is classified as a high viscosity tendency category, the I value of the actual lithium iron phosphate raw material is... D / I G The value will be less than the I value of lithium iron phosphate raw materials in the benchmark category. D / I G Value, at this time, the I value of lithium iron phosphate raw materials in the benchmark category D / I GA value of 0.86 ensures that the adjusted slurry viscosity matches the baseline category while avoiding excessive adjustment that could negatively impact the slurry's solids content. Similarly, when the actual lithium iron phosphate raw material is classified as a low-viscosity-prone category, the Ig of the actual lithium iron phosphate raw material... D / I G The value will be greater than the I value of lithium iron phosphate raw materials in the benchmark category. D / I G Value, at this time, the I value of lithium iron phosphate raw materials in the benchmark category D / I G The value is 0.89.
[0026] According to a second aspect of this application, a slurry viscosity control system is provided, which applies the above-described slurry viscosity control method. The slurry viscosity control system includes: The detection and acquisition module is used to detect the actual graphitization order of lithium iron phosphate raw materials.
[0027] The decision module categorizes lithium iron phosphate (LFP) raw materials into different viscosity tendency categories based on their actual graphitization order, and determines the solvent compensation amount based on the viscosity tendency category of the LFP raw material and its difference from a preset range. The control and execution module includes a batching unit, which controls the batching unit to feed materials to prepare slurry based on a determined solvent compensation amount.
[0028] Based on the embodiments described above, a slurry viscosity control system is disclosed, which can apply the aforementioned slurry viscosity control method. Specifically, the slurry viscosity control system includes a detection and acquisition module, a decision-making module, and a control execution module, which respectively implement each step of the aforementioned slurry viscosity control method.
[0029] Specifically, a detection and acquisition module is set up to detect the graphitization order of lithium iron phosphate raw materials before slurry preparation. Then, a decision module is set up to receive the detection data and classify the viscosity tendency of lithium iron phosphate raw materials. Subsequently, the decision module determines the solvent compensation amount based on the viscosity tendency of lithium iron phosphate raw materials and the difference between it and the preset range. Finally, the control and execution module accurately dispenses materials based on the solvent compensation amount so that the viscosity of the final battery slurry tends to be consistent.
[0030] In some embodiments, the detection and acquisition module is configured as a Raman spectrometer.
[0031] Based on the embodiments described above in this application, the detection and acquisition module is specifically configured as a Raman spectrometer, thereby accurately and quickly measuring the I content of lithium iron phosphate raw materials. D / I G This value is used to classify the viscosity tendency of lithium iron phosphate raw materials and calculate the solvent compensation amount.
[0032] According to a third aspect of this application, an electrode preparation process is provided, which utilizes the above-mentioned slurry viscosity control system. The electrode preparation process includes: In the slurry preparation, a slurry viscosity control system is used to feed lithium iron phosphate raw materials and solvents through a batching unit to prepare the positive electrode slurry.
[0033] Slurry coating: The positive electrode slurry is coated onto the positive electrode current collector to form a coarse positive electrode sheet.
[0034] Roll forming and cutting: The raw material of the positive electrode sheet is rolled and cut to prepare the positive electrode sheet.
[0035] Based on the above embodiments of this application, the electrode preparation process disclosed in this application uses the above-mentioned slurry viscosity control system. Through the above settings, the viscosity stability of the prepared positive electrode slurry can be improved, thereby ensuring the coating quality, improving the consistency of the prepared positive electrode, reducing the risk of lithium plating, and extending the cycle life of the electrode.
[0036] In some embodiments, the solvent is configured as N-methylpyrrolidone.
[0037] Based on the embodiments described above, this application determines the viscosity tendency of the prepared slurry by detecting the graphitization order of the lithium iron phosphate raw material, and then adjusts the amount of solvent added accordingly to adjust the viscosity of the prepared slurry. In this case, the specific type of solvent can be selected with reference to the prior art; specifically, N-methylpyrrolidone can be selected.
[0038] Other features and advantages of this application will be described in detail in the following detailed description section. Attached Figure Description
[0039] The accompanying drawings are provided to further illustrate the present application and form part of the specification. They are used together with the following detailed description to explain the present application, but do not constitute a limitation thereof. In the drawings: Figure 1 This is a schematic flowchart of the slurry viscosity control method provided in this application. Detailed Implementation
[0040] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0041] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. The components of the embodiments of this application described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.
[0042] Therefore, the following detailed description of the embodiments of this application provided in the accompanying drawings is not intended to limit the scope of the claimed application, but merely to illustrate selected embodiments of the application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without inventive effort are within the scope of protection of this application.
[0043] It should be noted that similar labels and letters in the following figures indicate similar items. Therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.
[0044] In the description of this application, it should be noted that, unless otherwise stated, the terms "inner," "outer," etc., indicating the orientation or positional relationship are based on the orientation or positional relationship shown in the accompanying drawings, or the orientation or positional relationship commonly used when the product is in use. They are used only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation on this application. In addition, the terms "first," "second," etc., are used only to distinguish descriptions and should not be construed as indicating or implying relative importance.
[0045] In the description of this application, it should also be noted that, unless otherwise expressly specified and limited, the terms "setup" and "connection" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this application according to the specific circumstances.
[0046] In the industrial production of lithium batteries, lithium iron phosphate is typically synthesized first using a liquid-phase method, followed by the preparation of the cathode slurry. During this process, fluctuations in the liquid-phase method can lead to intrinsic differences in the carbon coating thickness and microstructure of different batches of lithium iron phosphate raw materials. This, in turn, results in differences in the viscosity of the prepared cathode slurry. The viscosity difference of the cathode slurry directly affects the coating quality of the cathode sheet and the consistency of the subsequently manufactured batteries.
[0047] In existing technologies, the viscosity of the prepared cathode slurry is adjusted by fixing the formula and then manually adjusting it afterward. However, this method is not only inefficient, but may also require repeated adjustments and easily leads to waste of raw materials, resulting in increased costs.
[0048] Therefore, there is an urgent need to provide a process for preparing or controlling the positive electrode slurry, which can precisely adjust the viscosity of the prepared positive electrode slurry in advance, and achieve efficient and accurate slurry viscosity adjustment to improve the coating quality of the positive electrode sheet and the consistency of the manufactured battery.
[0049] To address the aforementioned problems in the prior art, this application provides a method for controlling slurry viscosity, referring to... Figure 1 As shown, the methods for adjusting slurry viscosity include: S001 Raw Material Testing: The actual graphitization order of lithium iron phosphate raw materials is determined.
[0050] S002 raw material classification: Based on the comparison between the actual graphitization order of lithium iron phosphate raw materials and the preset range, lithium iron phosphate raw materials are classified into different viscosity tendency categories.
[0051] S003 Solvent compensation determines the amount of solvent compensation based on the viscosity tendency category of the lithium iron phosphate raw material and its difference from a preset range.
[0052] S004 compensation execution: Based on the determined solvent compensation amount, the batching unit is controlled to feed materials to prepare the slurry.
[0053] Based on the above embodiments of this application, the graphitization order of lithium iron phosphate raw materials is measured before slurry preparation. The lithium iron phosphate raw materials are classified into different viscosity tendency categories according to the graphitization order. During slurry preparation, the graphitization order of lithium iron phosphate raw materials will directly affect the viscosity of the prepared slurry.
[0054] Specifically, on the one hand, when the graphitization order of lithium iron phosphate raw materials is higher, the particles in the lithium iron phosphate raw materials are more likely to agglomerate to form larger secondary particle agglomerates. At this time, the large-sized secondary particle agglomerates will increase the resistance to particle movement in the slurry, thereby increasing the slurry viscosity. Conversely, the slurry viscosity will decrease.
[0055] On the other hand, the higher the graphitization order of lithium iron phosphate raw materials, the higher the carbon content on the surface of lithium iron phosphate raw materials, and the more ordered and dense the carbon layer structure formed, which makes the interaction force between lithium iron phosphate particles and solvent stronger, thus making the viscosity of the prepared slurry higher, and vice versa.
[0056] As shown above, by detecting the graphitization degree of lithium iron phosphate raw materials, the viscosity of the prepared slurry can be effectively determined, allowing for solvent compensation in advance. For lithium iron phosphate raw materials with high graphitization degree, positive solvent compensation is performed by increasing the solvent content to reduce the viscosity of the prepared slurry. For lithium iron phosphate raw materials with low graphitization degree, negative solvent compensation is performed by reducing the solvent content to increase the viscosity of the prepared slurry. For lithium iron phosphate raw materials with graphitization degree within a preset range, the standard amount of solvent can be added. Ultimately, this ensures that the viscosity of the slurry prepared from different lithium iron phosphate raw materials tends to be consistent, guaranteeing the stability of the slurry viscosity.
[0057] In summary, this application pre-detects the graphitization order of lithium iron phosphate raw materials and pre-determines the viscosity of the prepared slurry based on the graphitization order of the lithium iron phosphate raw materials. Subsequently, when the slurry preparation begins, compensation adjustments can be made by adjusting the amount of solvent added, so that the viscosity of the slurry prepared from different lithium iron phosphate raw materials can tend to be consistent, ensuring the stability of the slurry viscosity, guaranteeing the coating quality of the electrode sheets, and ensuring the consistency of the batteries subsequently prepared.
[0058] Furthermore, in some embodiments of this application, during the raw material classification step, the actual graphitization order of the lithium iron phosphate raw material can be divided into three categories according to a preset range: a high viscosity tendency category, a baseline category, and a low viscosity tendency category. Specifically, in the high viscosity tendency category, the graphitization order of the lithium iron phosphate raw material is greater than the preset range; in the baseline category, the graphitization order of the lithium iron phosphate raw material is within the preset range; and in the low viscosity tendency category, the graphitization order of the lithium iron phosphate raw material is less than the preset range.
[0059] Based on the embodiments described above, lithium iron phosphate raw materials are specifically divided into three categories according to their graphitization degree. Specifically, a baseline category is first determined, and the viscosity of the slurry prepared from lithium iron phosphate raw materials within this baseline category corresponds to the baseline viscosity. Then, lithium iron phosphate raw materials with a graphitization degree greater than the baseline category are classified into a high viscosity tendency category. The slurry viscosity prepared from lithium iron phosphate raw materials in this category will be greater than the baseline viscosity; therefore, in subsequent preparation, it is necessary to reduce the viscosity of the prepared slurry by increasing the solvent. Finally, lithium iron phosphate raw materials with a graphitization degree less than the baseline category are classified into a low viscosity tendency category. The slurry viscosity prepared from lithium iron phosphate raw materials in this category will be less than the baseline viscosity; therefore, in subsequent preparation, it is necessary to increase the viscosity of the prepared slurry by reducing the solvent.
[0060] In some embodiments of this application, the Raman spectrum of lithium iron phosphate feedstock in the high viscosity tendency category contains I D / IG ≤0.85, in the Raman spectrum of lithium iron phosphate raw materials in the benchmark category, 0.85 < I D / I G <0.9, the Raman spectrum of lithium iron phosphate raw materials in the low viscosity tendency category has I D / I G ≥0.9.
[0061] Specifically, I in the above Raman spectrum D / I G This refers to the ratio of the D peak to the G peak in the Raman spectrum of lithium iron phosphate raw materials. The G peak refers to the peak at 1600 cm⁻¹ in the Raman spectrum. -1 The nearby peaks, specifically the G peak, represent the graphitized ordered structure of lithium iron phosphate raw materials. A larger G peak indicates a more orderly arrangement of carbon atoms in the surface carbon layer of the lithium iron phosphate raw material. The D peak refers to the peak at 1345 cm⁻¹ in the Raman spectrum. -1 The nearby peaks, particularly the D-peak, represent defects and disordered structures in the lithium iron phosphate raw material. A larger D-peak indicates greater defects and more disordered structures in the surface carbon layer. Therefore, the I-peak in the Raman spectrum corresponding to the lithium iron phosphate raw material... D / I G A higher I value indicates more defects in the surface carbon layer and a larger disordered structure, which in turn leads to a lower viscosity of the prepared slurry. Conversely, a lower I value in the Raman spectrum indicates a lower viscosity. D / I G The smaller the value, the more ordered and dense the carbon layer on the surface of the lithium iron phosphate raw material, and the higher the viscosity of the prepared slurry.
[0062] Based on the above embodiments of this application, using the I in the Raman spectrum of lithium iron phosphate raw material... D / I G The value reflects the graphitization order of lithium iron phosphate raw materials. Specifically, Raman spectroscopy can be used for detection, thereby achieving standardized and precise detection of the graphitization order of lithium iron phosphate raw materials, and thus improving the accuracy of subsequent control processes.
[0063] The principle of the slurry viscosity control method disclosed in this application has been explained above. In actual slurry preparation, the viscosity can be controlled based on the above principle. Specifically, in some embodiments of this application, in the solvent compensation step, the actual amount of solvent added can be determined according to the following formula (1): (1) Where m is the actual amount of solvent added, m0 is the theoretical amount of solvent added, and k is the control coefficient, which is set to 1500. For lithium iron phosphate feedstock in the benchmark category I D / I G With the lithium iron phosphate raw material I D / I GThe difference.
[0064] Based on the above embodiments of this application, a specific formula for determining the actual amount of solvent added is disclosed. In the specific calculation, the theoretical amount of solvent to be added is first determined, and then based on the I value of lithium iron phosphate raw materials in the benchmark category... D / I G With the lithium iron phosphate raw material I D / I G The solvent compensation amount is calculated based on the difference. For lithium iron phosphate raw materials with high viscosity tendency, the slurry viscosity is reduced by increasing the solvent, while for lithium iron phosphate raw materials with low viscosity tendency, the slurry viscosity is increased by reducing the solvent, ultimately making the viscosity of the prepared slurry tend to be consistent.
[0065] It should be noted that the above formula (1) is used to calculate the actual amount of solvent added, while the solvent compensation amount is the difference between the actual amount of solvent added and the theoretical amount of solvent added.
[0066] Furthermore, in some embodiments of this application, the theoretical amount of solvent added, m0, is in a mass ratio of 1:10 to the lithium iron phosphate raw material.
[0067] Based on the above embodiments of this application, when calculating the actual amount of solvent added, the theoretical amount of solvent added is first quickly determined according to the above ratio, and then the theoretical amount of solvent added is substituted into the above formula to determine the actual amount of solvent added.
[0068] Specifically, in the actual preparation process, the theoretical amount of solvent added and the mass ratio of lithium iron phosphate raw material can be adjusted according to different solvent types and process requirements. The specific settings can be made according to the actual situation, and this application does not impose specific restrictions on this.
[0069] In some embodiments of this application, calculation At that time, the I value of lithium iron phosphate raw materials in the benchmark category corresponding to the high viscosity tendency category is... D / I G The value is 0.86, which is the I value of lithium iron phosphate raw materials in the benchmark category corresponding to the low viscosity tendency category. D / I G The value is 0.89.
[0070] Based on the above embodiments of this application, when determining the actual amount of solvent added, it is necessary to consider the I value of lithium iron phosphate raw materials in the benchmark category. D / I G Value and actual lithium iron phosphate raw material I D / I G The difference is calculated using the value. Specifically, when the actual lithium iron phosphate raw material is classified as a high viscosity tendency category, the I value of the actual lithium iron phosphate raw material is...D / I G The value will be less than the I value of lithium iron phosphate raw materials in the benchmark category. D / I G Value, at this time, the I value of lithium iron phosphate raw materials in the benchmark category D / I G A value of 0.86 ensures that the adjusted slurry viscosity matches the baseline category while avoiding excessive adjustment that could negatively impact the slurry's solids content. Similarly, when the actual lithium iron phosphate raw material is classified as a low-viscosity-prone category, the Ig of the actual lithium iron phosphate raw material... D / I G The value will be greater than the I value of lithium iron phosphate raw materials in the benchmark category. D / I G Value, at this time, the I value of lithium iron phosphate raw materials in the benchmark category D / I G The value is 0.89.
[0071] Specifically, taking 1000kg of lithium iron phosphate raw material as an example... D / I G Taking a value of 0.91 as an example, this lithium iron phosphate raw material belongs to the low viscosity tendency category. Therefore, the I value of lithium iron phosphate raw materials in the benchmark category is... D / I G If the value is 0.89, then the calculation yields... The value is -0.02. The theoretical amount of solvent added, m0, is 100kg. Then, by substituting into the above formula (1), the actual amount of solvent added, m, is 70kg.
[0072] For example, taking 1000kg of lithium iron phosphate raw material as an example... D / I G Taking a value of 0.82 as an example, this lithium iron phosphate raw material belongs to the high viscosity tendency category. Therefore, the I value of lithium iron phosphate raw materials in the benchmark category is... D / I G If the value is 0.86, then the calculation yields... The value is 0.04, the theoretical amount of solvent added m0 is 100kg, and then the actual amount of solvent added m can be calculated by substituting it into the above formula (1) as 160kg.
[0073] Based on the above-mentioned basic solution, according to the second aspect of this application, a slurry viscosity control system is provided, which applies the above-mentioned slurry viscosity control method. The slurry viscosity control system includes: The detection and acquisition module is used to detect the actual graphitization order of lithium iron phosphate raw materials.
[0074] The decision module categorizes lithium iron phosphate (LFP) raw materials into different viscosity tendency categories based on their actual graphitization order, and determines the solvent compensation amount based on the viscosity tendency category of the LFP raw material and its difference from a preset range. The control and execution module includes a batching unit, which controls the batching unit to feed materials to prepare slurry based on a determined solvent compensation amount.
[0075] Based on the embodiments described above, a slurry viscosity control system is disclosed, which can apply the aforementioned slurry viscosity control method. Specifically, the slurry viscosity control system includes a detection and acquisition module, a decision-making module, and a control execution module, which respectively implement each step of the aforementioned slurry viscosity control method.
[0076] Specifically, a detection and acquisition module is set up to detect the graphitization order of lithium iron phosphate raw materials before slurry preparation. Then, a decision module is set up to receive the detection data and classify the viscosity tendency of lithium iron phosphate raw materials. Subsequently, the decision module determines the solvent compensation amount based on the viscosity tendency of lithium iron phosphate raw materials and the difference between it and the preset range. Finally, the control and execution module accurately dispenses materials based on the solvent compensation amount so that the viscosity of the final battery slurry tends to be consistent.
[0077] In this application, the detection module, decision-making module, and control execution module can all be selected with any suitable structure. For example, in some embodiments of this application, the detection and acquisition module can be configured as a Raman spectrometer.
[0078] Based on the embodiments described above in this application, the detection and acquisition module is specifically configured as a Raman spectrometer, thereby accurately and quickly measuring the I content of lithium iron phosphate raw materials. D / I G This value is used to classify the viscosity tendency of lithium iron phosphate raw materials and calculate the solvent compensation amount.
[0079] Similarly, the decision module can be set as a programmable logic controller (PLC) or other components. At this time, the PLC receives the detection data from the Raman spectrometer and performs raw material classification according to the detection data. The lithium iron phosphate raw material is divided into different viscosity tendency categories and substituted into the above formula (1) to calculate the actual amount of solvent added. Then, the control and execution module performs precise feeding.
[0080] For the control and execution module, in actual use, the control and execution module should have functions such as accurate load bearing and accurate material feeding. The specific structure can be selected according to the actual situation. Since this application does not involve the improvement of this part, it will not be described in detail here.
[0081] Based on the above technical solutions, according to a third aspect of this application, an electrode preparation process is provided, which utilizes the aforementioned slurry viscosity control system. This electrode preparation process includes: In the slurry preparation, a slurry viscosity control system is used to feed lithium iron phosphate raw materials and solvents through a batching unit to prepare the positive electrode slurry.
[0082] Slurry coating: The positive electrode slurry is coated onto the positive electrode current collector to form a coarse positive electrode sheet.
[0083] Roll forming and cutting: The raw material of the positive electrode sheet is rolled and cut to prepare the positive electrode sheet.
[0084] Based on the above embodiments of this application, the electrode preparation process disclosed in this application uses the above-mentioned slurry viscosity control system. Through the above settings, the viscosity stability of the prepared positive electrode slurry can be improved, thereby ensuring the coating quality, improving the consistency of the prepared positive electrode, reducing the risk of lithium plating, and extending the cycle life of the electrode.
[0085] In the specific preparation process, steps such as slurry coating and roll cutting can be set with reference to existing technologies, including the roll pressure and cutting dimensions. Meanwhile, the positive electrode current collector can be made of materials such as aluminum foil.
[0086] Furthermore, it should be noted that the positive electrode slurry is not limited to the above components in the specific preparation process. For example, in some embodiments of this application, the positive electrode slurry may also include binders, conductive agents, and dispersants. Specifically, the binder may be any one or more of carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and polyacrylic acid (PAA); the conductive agent may be conductive carbon black and carbon nanotubes; and the dispersant may be any one or more of carboxymethyl cellulose (CMC), sodium polyacrylate (PAAS), and polyvinylpyrrolidone (PVP).
[0087] Similarly, in this application, any suitable solvent can be selected with reference to existing technologies. In this application, the viscosity tendency of the prepared slurry is determined by detecting the graphitization order of the lithium iron phosphate raw material, and then the amount of solvent added is adjusted accordingly to adjust the viscosity of the prepared slurry. In this case, the specific type of solvent can be selected with reference to existing technologies; specifically, N-methylpyrrolidone can be selected.
[0088] The performance of the negative electrode prepared by the electrode manufacturing process in this application will be further compared and illustrated through eight specific embodiments.
[0089] Example 1 A positive electrode slurry was prepared using lithium iron phosphate as the raw material and N-methylpyrrolidone as the solvent. The solvent was added according to the theoretical addition amount during preparation, and the viscosity of the prepared positive electrode slurry was measured. Subsequently, a positive electrode slurry was prepared again using the same lithium iron phosphate raw material and N-methylpyrrolidone as the solvent, and the viscosity was adjusted using the slurry viscosity control method disclosed in this application. The concentration of the prepared positive electrode slurry was measured again.
[0090] Specifically, the I of this lithium iron phosphate raw material D / I G The value is 0.9, the raw material mass is 1000kg, and the theoretical amount of solvent added is 100kg. Substituting into the above formula (1), it can be calculated that the actual amount of solvent added is 85kg.
[0091] Example 2 The preparation and testing process of Example 2 is the same as that of Example 1, except that the lithium iron phosphate raw material in Example 2 has I D / I G The value is 0.85. Substituting it into the above formula (1), we can calculate that the actual amount of solvent added is 115 kg.
[0092] Example 3 The preparation and testing process of Example 3 is the same as that of Example 1, except that the lithium iron phosphate raw material in Example 3 has I D / I G The value is 0.84. Substituting it into the above formula (1), we can calculate that the actual amount of solvent added is 130 kg.
[0093] Example 4 The preparation and testing process of Example 4 is the same as that of Example 1, except that the lithium iron phosphate raw material in Example 4 has I D / I G The value is 0.83. Substituting it into the above formula (1), we can calculate that the actual amount of solvent added is 145 kg.
[0094] Example 5 The preparation and testing process of Example 5 is the same as that of Example 1, except that the lithium iron phosphate raw material in Example 5 has I D / I G The value is 0.91. Substituting it into the above formula (1), we can calculate that the actual amount of solvent added is 70 kg.
[0095] Example 6 The preparation and testing process of Example 6 is the same as that of Example 1, except that the lithium iron phosphate raw material in Example 6 has I D / I G The value is 0.88, which is within the baseline range. Therefore, the actual amount of solvent added is the theoretical amount, which is 100 kg.
[0096] Example 7 The preparation and testing process of Example 7 is the same as that of Example 1, except that the lithium iron phosphate raw material in Example 7 has I D / I G The value is 0.89, which is within the baseline range. Therefore, the actual amount of solvent added is the theoretical amount, which is 100 kg.
[0097] Example 8 The preparation and testing process of Example 8 is the same as that of Example 1, except that the lithium iron phosphate raw material in Example 8 has I D / I G The value is 0.86, which is within the baseline range. Therefore, the actual amount of solvent added is the theoretical amount, which is 100 kg.
[0098] The table below shows the viscosity and solid content of the positive electrode slurry prepared in Examples 1-8.
[0099]
[0100] As shown in the table above, the slurries prepared from lithium iron phosphate raw materials in Examples 1-5 exhibited significant differences in viscosity before regulation, with the difference between the maximum and minimum viscosity reaching 41,300 mPa·s. However, after regulation using the slurry viscosity regulation method disclosed in this application, the slurry viscosity stabilized at approximately 17,000 mPa·s, and the difference between the maximum and minimum viscosity became 1,720 mPa·s. It is evident that the regulation described in this application can bring the originally significantly different slurry viscosities closer to uniformity, thereby ensuring the stability of the slurry viscosity, guaranteeing the coating quality of the electrode sheets, and ensuring the consistency of the subsequently prepared batteries.
[0101] Specifically, the lithium iron phosphate raw materials in Examples 1 and 5 both belong to the low viscosity tendency category, and the measured slurry viscosity before adjustment is low. This firstly verifies the I-based method in this application. D / I G The reliability of classifying the viscosity tendency of lithium iron phosphate raw materials was assessed. Furthermore, the slurry viscosities of Examples 1 and 5 after adjustment were 16700 mPa·s and 16360 mPa·s, respectively. The slurry viscosities in both examples were improved, and the improved slurry viscosities were relatively stable.
[0102] Similarly, in Examples 2, 3, and 4, the lithium iron phosphate raw materials all belong to the high viscosity tendency category, and the measured slurry viscosity before adjustment is relatively high. This also verifies the I-based method used in this application. D / I G The reliability of classifying the viscosity tendency of lithium iron phosphate raw materials was assessed. Furthermore, the slurry viscosities of Examples 2, 3, and 4 after adjustment were 17140 mPa·s, 16360 mPa·s, and 15420 mPa·s, respectively. The slurry viscosity in all three examples was reduced, and the increased slurry viscosity was relatively stable.
[0103] For Examples 6, 7, and 8, the lithium iron phosphate raw materials in the above three examples all belong to the benchmark category. Therefore, it is determined that the solvent can be added directly according to the theoretical addition amount. Subsequently, the slurry viscosity in the three examples was measured to be 16320 mPa·s, 15240 mPa·s, and 17180 mPa·s, respectively. The slurry viscosity corresponding to the above examples is not much different from the slurry viscosity after adjustment in Examples 1-5.
[0104] As can be seen, through the above-mentioned regulation in this application, regardless of the viscosity tendency of the lithium iron phosphate raw material, the viscosity of the slurry after regulation can tend to be consistent, thereby ensuring the stability of the slurry viscosity. At the same time, the solid content of the cathode slurry after regulation can be stabilized at around 67%, avoiding disruption of the solid content balance of the slurry during the regulation process.
[0105] The preferred embodiments of this application have been described in detail above with reference to the accompanying drawings. However, this application is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this application, various simple modifications can be made to the technical solution of this application, and these simple modifications all fall within the protection scope of this application.
[0106] It should also be noted that the various specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, this application will not describe the various possible combinations separately.
[0107] Furthermore, various different implementations of this application can be combined in any way, as long as they do not violate the spirit of this application, they should also be regarded as the content disclosed in this application.
Claims
1. A method for controlling the viscosity of a slurry, characterized in that, The slurry viscosity control method includes: Raw material testing was conducted to determine the actual graphitization order of lithium iron phosphate raw materials. The raw material is classified into different viscosity tendency categories by comparing the actual graphitization order of the lithium iron phosphate raw material with a preset range. Solvent compensation is determined based on the viscosity tendency category of the lithium iron phosphate raw material and its difference from a preset range. The compensation process involves controlling the feeding of materials in the batching unit to prepare the slurry based on the determined solvent compensation amount.
2. The slurry viscosity control method according to claim 1, characterized in that, In the raw material classification step, the actual graphitization order of the lithium iron phosphate raw material is divided into three categories according to the preset range. The three categories are high viscosity tendency category, benchmark category and low viscosity tendency category. Specifically, the graphitization order of the lithium iron phosphate raw material in the high viscosity tendency category is greater than the preset range, the graphitization order of the lithium iron phosphate raw material in the benchmark category is within the preset range, and the graphitization order of the lithium iron phosphate raw material in the low viscosity tendency category is less than the preset range.
3. The slurry viscosity control method according to claim 2, characterized in that, In the Raman spectrum of the lithium iron phosphate raw material in the high viscosity tendency category, I D / I G ≤0.85, where 0.85 < I in the Raman spectrum of the lithium iron phosphate raw material in the benchmark category. D / I G <0.9, the Raman spectrum of the lithium iron phosphate raw material in the low viscosity tendency category has I D / I G ≥0.
9.
4. The slurry viscosity control method according to any one of claims 1-3, characterized in that, In the solvent compensation step, the actual amount of solvent added is determined according to the following formula (1): (1) Where m is the actual amount of solvent added, m0 is the theoretical amount of solvent added, and k is the control coefficient, which is set to 1500. For lithium iron phosphate feedstock in the benchmark category I D / I G With the lithium iron phosphate raw material I D / I G The difference.
5. The slurry viscosity control method according to claim 4, characterized in that, The theoretical addition amount m0 of the solvent is in a mass ratio of 1:10 to the lithium iron phosphate raw material.
6. The slurry viscosity control method according to claim 4, characterized in that, Calculate the At that time, the lithium iron phosphate raw material in the benchmark category corresponding to the high viscosity tendency category of the lithium iron phosphate raw material is I D / I G The value is 0.86, which is the I value of lithium iron phosphate raw materials in the benchmark category corresponding to the low viscosity tendency category. D / I G The value is 0.
89.
7. A slurry viscosity control system, employing the slurry viscosity control method as described in any one of claims 1-6, characterized in that, The slurry viscosity control system includes: The detection and acquisition module is used to detect the actual graphitization order of the lithium iron phosphate raw material; The decision module is used to classify the lithium iron phosphate raw material into different viscosity tendency categories based on the actual graphitization order, and to determine the solvent compensation amount based on the viscosity tendency category of the lithium iron phosphate raw material and its difference from a preset range; and, The control and execution module includes a batching unit, which controls the batching unit to feed materials to prepare a slurry based on the determined solvent compensation amount.
8. The slurry viscosity control system according to claim 7, characterized in that, The detection and acquisition module is configured as a Raman spectrometer.
9. An electrode preparation process, employing the slurry viscosity control system as described in claim 7 or 8, characterized in that, The electrode preparation process includes: Slurry preparation: The slurry viscosity control system is used to feed lithium iron phosphate raw materials and solvents through the batching unit to prepare the positive electrode slurry. Slurry coating: The positive electrode slurry is coated onto the positive electrode current collector to form a coarse positive electrode sheet. Roll forming and cutting: The raw material of the positive electrode sheet is rolled and cut to prepare the positive electrode sheet.
10. The electrode preparation process according to claim 9, characterized in that, The solvent is configured as N-methylpyrrolidone.